The Vegetation of the South Shetland Islands and the Climatic Change - Putzke, Jair (2019)
Antarctica allows at the same time to study the effects of change on the environment with minimal anthropic interference and in the least modified conditions in the world regarding biodiversity and its relations. At the same time, it allows assessing its effects on an ecosystem of few species and with a food web that directly links the oceans to terrestrial organisms. The South Shetland Islands are located further north within Antarctic Maritime and are therefore more vulnerable to climate change. Part of the studies already carried out with vegetation in this archipelago are discussed with a focus on the effects already generated and on predictions about future changes in the structure and plant diversity of Antarctica.